Peranan Bank Syariah Sebagai Investment Intermediary Dalam Meningkatkan Kesejahteraan Masyarakat - Harfandi, Harfandi (Jurnal Ekonomi, 2012)
The role of syaria banking as an intermediary investment was, required, especially for improving of the prosperity of society, that can be done by implementation of mudaraba financing or musyarakah financing. By canneling the both of this type of financing, all the investment was intructed fully to run the business. Changing and priority in channeling of the bank's fund are really determine the role of the syaria banking, in the case of improving the development of economics and prosperity of society. By changing the habit of the syaria bank which tend to give loan as a consumptive loan, and replace being a productive loan by using mudharabah or musyarakah will give the impact to the developer of corporate world, increasing the employment, decreasing of infliation rate, make-up of growth of national product, and improvment of the prosperity of society.